Research progress of doctor-nurse integration model in pulmonary rehabilitation for children with chronic respiratory disease (医护一体化在慢性呼吸道疾病儿童呼吸康复训练中的应用进展) - HUANG Rulin (黄儒霖); QIN Yi (秦怡); NING Jianhui (宁建辉); MA Lan (马兰); XU Xuehua (徐雪花); LU Gen (卢根); FAN Huifeng (樊慧峰) (中西医结合护理)
Pulmonary rehabilitation plays a key role in the management of children with chronic respiratory diseases. The efficacy of respiratory rehabilitation is influenced by a variety of factors, such as the knowledge of respiratory rehabilitation mastered by healthcare personnel, the understanding and cooperation of children and their parents with respiratory rehabilitation, and the accuracy and continuity of the rehabilitation training. The doctor-nurse integration model focuses on the synergy between healthcare personnel and emphasizes the systematic and holistic management of children, which helps to improve the overall efficacy of respiratory rehabilitation. This paper systematically reviewed studies on clinical practice of the doctor-nurse integration model in the respiratory rehabilitation training of children with chronic respiratory diseases. It provided a theoretical basis for clinical practice, further optimizing the cooperation between healthcare professionals and maximizing the efficacy of respiratory rehabilitation, and providing a more scientific and effective support for the pulmonary rehabilitation management of children with chronic respiratory diseases. (呼吸康复在慢性呼吸道疾病儿童的管理中发挥着关键作用。呼吸康复的疗效受到医护人员对呼吸康复知识的掌握程度、患儿及其家长对呼吸康复的了解度与配合度、康复训练动作的准确性以及训练的持续性等多种因素的综合影响。医护一体化模式注重医护人员之间的协同合作, 强调要对患儿实施系统化、全程化的管理, 有助于提升呼吸康复的整体疗效。本文系统探讨医护一体化模式在儿童慢性呼吸道疾病呼吸康复训练中的应用现状, 以期为临床实践提供理论依据, 进一步优化医护配合, 从而最大化呼吸康复的疗效, 为慢性呼吸道疾病儿童的康复提供更为科学、有效的支持。)